2022
DOI: 10.1038/s41388-022-02295-w
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin enhances mesenchymal features of glioblastoma by establishing autocrine and paracrine networks in a CMKLR1-dependent manner

Abstract: Glioblastoma multiforme (GBM) with mesenchymal features exhibits enhanced chemotherapeutic resistance and results in reduced overall survival. Recent studies have suggested that there is a positive correlation between the GBM mesenchymal status and immune cell infiltration. However, the mechanisms by which GBM acquires its mesenchymal features in a tumor immune microenvironment-dependent manner remains unknown. Here, we uncovered a chemerin-mediated autocrine and paracrine network by which the mesenchymal phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…To investigate whether RARRES2 could have a similar effect on other CSCs, we focused on the role of the IGF1–RARRES2 axis in the TAM–CSC interaction by restoring intercellular communication. The chemerin/CMKLR1 axis promotes the interaction between glioblastoma (GBM) cells and TAMs by activating NF-κB signaling 75 . In addition, previous studies have shown that TAMs can promote metastasis and help maintain the stemness of thyroid cancer cells by secreting IGF 76 .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether RARRES2 could have a similar effect on other CSCs, we focused on the role of the IGF1–RARRES2 axis in the TAM–CSC interaction by restoring intercellular communication. The chemerin/CMKLR1 axis promotes the interaction between glioblastoma (GBM) cells and TAMs by activating NF-κB signaling 75 . In addition, previous studies have shown that TAMs can promote metastasis and help maintain the stemness of thyroid cancer cells by secreting IGF 76 .…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that RARRES2 knockdown can significantly reduce GBM cell viability and proliferation activity, and the protein expression level of RARRES2 was significantly correlated with IDH status in GBM patients. Although RARRES2 has different expression patterns in different tumors, RARRES2 can promote GBM mesenchymal properties by inhibiting the ubiquitin‒proteasome degradation of CMKLR1 [ 42 ], which indicates that RARRES2 can support tumor progression in GBM. Our results also demonstrated that the expression of RARRES2 in GBM was positively correlated with TME scores and M0 macrophage infiltration and positively correlated with the expression of immune checkpoints, such as PD-L1 (CD274).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed protocol of flow cytometry was performed as previously described ( 51 ). FACS data were analyzed through FlowJo software (version 10.4).…”
Section: Methodsmentioning
confidence: 99%